Analyzing passive solar strategies in the case of high-rise building - Lotfabadi, Pooya (Pergamon-Elsevier Science Ltd, 2015)
Nowadays, societies are not able to live without energy. After 1970's energy crises, energy has become a more serious issue and environmental protection is one of the most important considerations in countries' sustainable development. Different types of energies such as thermal, electricity and so on are used in people's daily lives. Many of these energy types are derived from sedimentary sources like oil, gas and coal, which are not interminable. So, one of the fundamental challenges of today's world is seeking renewable energy alternatives such as solar, wind, hydro, biomass, geothermal and so on, to replace the fossil fuels. This attempt should be done in all sections like transportation, industry, buildings and etc. Building section is one of the greatest energy consumer sectors. In this sector, high-rise buildings with their vast facades have a great potential to consume sustainable energies. For instance they can easily gain solar radiations. Thus, here, the emphasis has been put on the practices and attempts done to take advantages of solar radiation as an energy source in high-rise buildings. Although there are many appreciable scientific solutions for energy efficiency problems, there are still huge gaps, especially negligence in analyzing the effectiveness of different passive solar strategy criteria, found in high-rise buildings as an imminent part of a new society. Therefore, the authors' main attempt is to understand how passive solar design strategies are implemented in the case study, the Frankfurt Commerzbank Tower. This has been done to obtain an environmental friendly pattern of high-rise buildings. This study is based on a theoretical approach supported mainly by the outcomes of literature review and case study analysis from the solar design aspects. The results of this research show that sustainable skyscrapers, which benefit from solar energy design, can be more energy efficient, using different solar passive strategies. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: High-rise buildings; Renewable energies; Passive solar strategies; Frankfurt Commerzbank